Analisis Karyotipe Bawang Merah Hasil Persarian Bebas - Andrean H. Wospakrik (Agrotek, 2017)
Three varieties of seed origin shallot, namely Biru, Tiron and Tutuk were grown to be taken their roots for chromosom observation. The ratio of Chromosom arm obtained would be used for: (1) determine chromosome shape based on centromere position, (2) the homologous chromosome pair, (3) karyoptype composition. The result revealed showed that the chromosome number of the three varieties of shallot were 16 with the formula of chromosome is 2n = 2x = 16. The ration of arm length of the three varieties formed the same chromosome formula: 4M (metacentric) + 3SM (submetacentric) + 1ST (subtelocentric). This results revealed that the open pollinated shallot would form the similar karyotype with the parents.